Tectonic burial of sedimentary rocks drives the building of juvenile crust of magmatic arc - Qin, SK; Zhang, ZM; Palin, RM; Ding, HX; Dong, X; Tian, ZL (Geological Society of America, 2022)
Continental arcs grow primarily by addition of mantle-derived magmas, thus forming juvenile crust, although geophysical evidence, alongside field investigation of exhumed terranes, show that supracrustal rocks are common components of the lower portions of continental arcs. The mechanisms by which metasedimentary rocks are transported to the deep arc crusts and their contributions to the juvenile arc crusts are ambiguous. Here, we conduct a systematic petrological, geochronological, and geochemical study of pelitic migmatites within Late Cretaceous meta-gabbros from the lower crust of the eastern Gangdese arc, southern Tibet. Our results show that the pelitic migmatites were derived from the Late Carboniferous sedimentary rocks of the upper arc crust, have significantly enriched Sr-Nd-Hf-O isotopic compositions, and underwent Late Cretaceous (95–80 Ma) high-pressure granulitefacies metamorphism and partial melting at ∼850 °C and 15 kbar to generate voluminous granitic melts. This indicates that the eastern Gangdese arc underwent significant crustal thickening and chemical differentiation during the final stages of subduction of the Neo-Tethys. We suggest that the metasedimentary rocks were transported into the lower crust of the Gangdese arc by underthrusting of arc crust and accretion of mantle-derived magma, and the deeply buried supracrustal rocks altered the petrological constitution and chemical compositions of juvenile lower arc crust, and assimilated the mantle and juvenile crust-derived melts. We propose that tectonic burial of sedimentary rocks is a key mechanism driving the building and reworking of juvenile crust of magmatic arcs throughout most of geological time.